2005
DOI: 10.1002/pros.20341
|View full text |Cite
|
Sign up to set email alerts
|

Time course of serum testosterone and luteinizing hormone levels after cessation of long‐term luteinizing hormone‐releasing hormone agonist treatment in patients with prostate cancer

Abstract: Long-term LH-RH agonist therapy has remarkable effects on serum T level that last for a significant time after cessation, a fact that should be applied to the interpretation of both PSA and serum T levels after cessation of androgen deprivation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 15 publications
5
59
0
Order By: Relevance
“…[3][4][5][6][7]9,21,22 Therefore, it is not surprising that a correlation between patient baseline testosterone level and timing of testosterone normalization was found in this study. We failed to demonstrate a correlation between age and timing of testosterone normalization in our patients.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…[3][4][5][6][7]9,21,22 Therefore, it is not surprising that a correlation between patient baseline testosterone level and timing of testosterone normalization was found in this study. We failed to demonstrate a correlation between age and timing of testosterone normalization in our patients.…”
Section: Discussionsupporting
confidence: 56%
“…However, when it comes to long-term ADT, things become complicated. In a study which included 32 patients who received ADT for a minimum of 2 years (24-87 months) as an adjuvant therapy for RP or external beam radiation therapy (EBRT), Kaku et al 7 revealed that it took 30 months for more than 90% patients to recover to supracastrate testosterone level. Yoon et al 4 also reported that after 2 years of adjuvant ADT for PCa patients underwent RP, it took 36 months for 93.2% patients to recover to supracastrate testosterone level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations